Archaeology and gastronomy: Uncovering the historical roots of food security in cultural heritage tourism - Kulyniak, Ihor; Dziurakh, Yurii; Lagodiienko, Volodymyr; Tomashevskyi, Yurii; Sembay, Nataliya (Research Journal in Advanced Humanities, 2024)
This research is intended to use archaeology and gastronomy to understand the historical origins of food security in historical heritage tourism. By looking at ancient foods and their modern applications, we want to bring out how those foods can help drive modern food security. The study employs qualitative interviews with archaeologists and food historians and quantitative questionnaires distributed to tourists engaged in cultural heritage activities. NVivo software was used to analyze qualitative data, while SPSS was used to analyze quantitative data. This study shows an excellent fit between older food habits and recent food security beliefs among travelers. The research also discovers a few of the most significant archaeological sites, which serve as attractions for gastronomic tourism, facilitating visitors’ attraction and information. The article suggests that cultural heritage tourism enhanced through archaeological knowledge in gastronomy can also add to sustainable food security programs. This study can be applied in cultural heritage management, food security policy, tourism planning, and implementation to create a better visitor experience and sustainable living. The novelty of this research is in the connection of archaeological knowledge to modern food security concerns in a manner that challenges the understanding currently held by archaeology and gastronomy.